The Multispecies Salon - Kirksey, Eben, 1976- (Book collections on Project MUSE., 2014)
A new approach to writing culture has arrived : multispecies ethnography. Plants, animals, fungi, and microbes appear alongside humans in this singular book about natural and cultural history.